The Theological Roots of Christian Gratitude - Wilson, Kenneth. author. aut Link
VIII, 239 p.
Keywords: This book asserts that gratitude for God's gift of creation grounds the insight of positive psychology that grateful persons act pro-socially. Kenneth Wilson posits that a sense of gratitude encourages sacrificial service and reveals all behavior to have at heart an essential moral quality.